2011
DOI: 10.1007/s12015-011-9292-0
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Estrogen on Bone Marrow-Derived Rat Mesenchymal Stem Cell Maintenance: Inhibiting Apoptosis Through the Expression of Bcl-xL and Bcl-2

Abstract: Mesenchymal Stem Cells (MSCs) have high therapeutic value for regenerative medicine and tissue engineering due to their differentiation potential and nonimmunogenic characteristics. They are also considered as an effective in vivo delivery agent because of their ability to migrate to the site of injury. A major roadblock in their use for cell-based therapies is their rareness in vivo. Therefore, it is important to obtain increased number of functional MSCs in vitro in order to have adequate numbers for therape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…Although, E2 is not a recommended treatment for fracture healing, a recent study showed improvement in fracture healing based on histological and biomechanical parameters in Ovx rats treated with E2, thus suggesting a positive role of the hormone in promoting fracture healing [43]. However, the reported study used a prophylactic design where E2 treatment was given to rats soon after Ovx without allowing the time for osteopenia to develop.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although, E2 is not a recommended treatment for fracture healing, a recent study showed improvement in fracture healing based on histological and biomechanical parameters in Ovx rats treated with E2, thus suggesting a positive role of the hormone in promoting fracture healing [43]. However, the reported study used a prophylactic design where E2 treatment was given to rats soon after Ovx without allowing the time for osteopenia to develop.…”
Section: Discussionmentioning
confidence: 98%
“…Reduced MSC population in the Ovx rats could be due to apoptosis as E2 at a pharmacological concentration (10 −7 M) has been shown to exert anti-apoptotic/prosurvival effect on MSC in vitro [43]. In postmenopausal women, osteoporosis delays fracture healing and causes reduced bone deposition [44], and together, the recovery of functional competence of the fractured bone in osteoporotic women is delayed [22].…”
Section: Discussionmentioning
confidence: 99%
“…ASCs and BMSCs share common characteristics, including growth and morphology [31], displaying fibroblastic features, and a similar transcriptional and cell surface marker expression profile [32]. At present, much of the research is mainly focusing on the effects and mechanisms of estrogen and its receptors for improving BMSC behavior in tissue engineering applications [33]. Although an ideal cell type for transplantation due to availability of convenient methods and their presence in large cell quantities, ASCs still remain elusive with respect to effects mediated by estrogen receptor α and β.…”
Section: Discussionmentioning
confidence: 99%
“…Due to this differentiation potential combined with their nonimmunogenic characteristics, MSCs are promising therapeutic tools in regenerative medicine 2 ISRN Stem Cells and tissue engineering [6][7][8][9] and thus also for therapeutic strategies in osteoporotic patients.…”
Section: Introductionmentioning
confidence: 99%